2021
DOI: 10.1177/1475921720984431
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and visualization of performance indicators of reinforced concrete beams by distributed optical fibre sensing

Abstract: The implementation of structural health monitoring systems in civil engineering structures already in the construction phase could contribute to safer and more resilient infrastructure. Due to their lightweight, small size and high resistance to the environment, distributed optical fibre sensors stand out as a very promising technology for damage detection and quantification in reinforced concrete structures. In this article, the suitability of embedding robust distributed optical fibre sensors featuring a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 36 publications
5
40
0
Order By: Relevance
“…In a previous study by the authors [ 25 ], it was shown that when using robust fiber optic sensors embedded in concrete, most cracks could be clearly identified in the strain profiles as regions of strain localization and that the integration of the strain curve, within a neighboring region of the crack, provided a good approximation of the individual crack width without the need of additional analytical models. In the same study, it was demonstrated that when bending is dominant, performing a double integration of the curvature distribution, calculated from the strain distribution at two different heights of the beam, provides an accurate estimation of the deflections, given the right boundary conditions are applied.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study by the authors [ 25 ], it was shown that when using robust fiber optic sensors embedded in concrete, most cracks could be clearly identified in the strain profiles as regions of strain localization and that the integration of the strain curve, within a neighboring region of the crack, provided a good approximation of the individual crack width without the need of additional analytical models. In the same study, it was demonstrated that when bending is dominant, performing a double integration of the curvature distribution, calculated from the strain distribution at two different heights of the beam, provides an accurate estimation of the deflections, given the right boundary conditions are applied.…”
Section: Introductionmentioning
confidence: 99%
“…A good agreement (±20 μm) was generally observed between DOFS and DIC crack widths monitoring, as can be seen in Figure 14. Berrocal et al [60] also investigated the suitability of embedded robust OFDR DOFS (featuring a protective external rugged polyamide coating) to accurately assess the per- This range is understandable considering the different depths at which the transversal cracks were measured and their probable lack of perpendicularity compared to the beams' axis. An additional takeaway was the need for a certain amount of strain noise-removing data post-processing in order to determine the crack position.…”
Section: Reinforced Concrete Beams: Cracking and Other Serviceabilitymentioning
confidence: 99%
“…Berrocal et al [60] also investigated the suitability of embedded robust OFDR DOFS (featuring a protective external rugged polyamide coating) to accurately assess the performance requirements, in terms of vertical deflection and crack width, of three 20 × 25 × 300 cm RC beams subjected to four-point bending. The strain measurements performed by means of the thicker fiber were additionally integrated with the ones extracted from thin polyamide-cladded ones and from an external DIC system.…”
Section: Reinforced Concrete Beams: Cracking and Other Serviceabilitymentioning
confidence: 99%
See 2 more Smart Citations